Early Brain Sensitivity to Word Frequency and Lexicality During Reading Aloud and Implicit Reading - Faísca, Luís; Reis, Alexandra; Araújo, Susana (Frontiers in Psychology, 2019)
The present study investigated the influence of lexical word properties on the early stages of visual word processing (< 250ms), and how the dynamics of lexical access interact with task-driven top-down processes. We compared the brain’s electrical response (event-related potentials, ERPs) of 39 proficient adult readers for the effects of word frequency and word lexicality during an explicit reading task versus a visual immediate-repetition detection task where no linguistic intention is required. In general, we observed that left-lateralized processes linked to perceptual expertise for reading are task-independent. Moreover, there was no hint of a word frequency effect in early ERPs, while there was a lexicality effect which was modulated by task demands: during implicit reading, we observed larger N1 negativity in the ERP to real words compared to pseudowords, but in contrast this modulation by stimulus type was absent for the explicit reading aloud task (where words yielded the same activation as pseudowords). Thus, data indicate that the brain’s response to lexical properties of a word is open to influences from top-down processes according to the representations that are relevant for the task, and this occurs from the earliest stages of visual recognition (within 200ms). We conjectured that the loci of these early top-down influences identified for implicit reading are probably restricted to lower levels of processing (such as whole word orthography) rather than the process of lexical access itself.